Determinants of the Quality of Warfarin Control after Venous Thromboembolism and Validation of the SAMe-TT2-R2 Score: An Analysis of Hokusai-VTE - Barco, Stefano; Granziera, Serena; Coppens, Michiel; Douxfils, Jonathan; Nijkeuter, Mathilde; Riva, Nicoletta; Vanassche, Thomas; Zhang, George; Lin, Min; Kamphuisen, Pieter W.; Cohen, Alexander T.; Beyer-Westendorf, Jan (Thrombosis and Haemostasis, 2019)
Background Time in therapeutic range (TTR) measures the quality of vitamin K antagonist (VKA) anticoagulation. In patients with atrial fibrillation, the dichotomized SAMe-TT2-R2 score (≥2 vs. < 2 points) can predict if adequate TTR is unlikely to be achieved.Aims We validated the SAMe-TT2-R2 score in patients with venous thromboembolism (VTE) randomized to the warfarin arm of the Hokusai-VTE trial.Patients and Methods A total of 3,874 patients were included in the primary analysis (day 31–180 from randomization). The efficacy and safety outcomes were symptomatic recurrent VTE and major or clinically relevant non-major bleeding.Results The rates of recurrent VTE and bleeding events were higher in patients with a TTR below the median (< 66% vs. ≥66%) resulting in an absolute risk difference (ARD) of +0.5% (95% confidence interval: 0%, +1.1%) and +2.2% (0.9%, +3.5%), respectively. Patients with high SAMe-TT2-R2 score were 76% of total and had lower median TTR (64.7% vs. 70.7%). The SAMe-TT2-R2 score exhibited low negative (0.59) and positive (0.52) predictive value (TTR threshold 66%), and poor discrimination (c-statistic, 0.58). ARD between patients with high and low score was 0% (–0.6%, +0.7%) for recurrence and +1.3% (–0.1%, +2.7%) for bleeding. Results were confirmed in sensitivity analyses focusing on the whole study period (day 1–365).Conclusion In VTE patients, the SAMe-TT2-R2 score showed unsatisfactory discrimination and predictive value for individual TTR and did not correlate well with clinical outcomes. The choice of starting a patient on VKA cannot be based on this parameter and its routine use after VTE may not translate into clinical usefulness.
Keywords: vitamin K antagonist; quality of treatment; warfarin; venous thromboembolism; risk assessment model